Study of performance and emission characteristics of a single cylinder CI engine using diethyl ether and ethanol blends. Issue 1 (February 2015) - Paul, Abhishek; Bose, Probir Kumar; Panua, RajSekhar; Debroy, Durbadal
Abstract In this paper, the performance and emission of a single cylinder Diesel engine has been studied by using the blends of Diesel–diethyl ether (DEE) and Diesel–diethyl ether–ethanol. The used blends are D95DEE5 (5% DEE, 95% Diesel by volume), D90DEE10 (10% DEE, 90% Diesel by volume), D90DEE5E5 (5% ethanol, 5% DEE and 90% Diesel by volume), D85DEE5E10 (10% ethanol, 5% DEE and 85% Diesel by volume), D85DEE10E5 (5% ethanol, 10% DEE and 85% Diesel by volume) and D80DEE10E10 (10% ethanol, 10% DEE and 80% Diesel by volume). The thermal efficiency of the engine increased with the blend of 5% DEE blend whereas, decreased with 10% DEE blend. Ethanol addition to Diesel–DEE blends increased the efficiency of the engine for both the cases. Use of ethanol along with DEE reduced CO, NOx, hydrocarbon and particulate matters remarkably. Blend D80DEE10E10 showed the best potential of achieving the paradoxical objective of high performance with low emission among the tested fuel samples.